(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to de termine how employee performance and its influence on patient satisfaction in Labuang Baji Makassar.hospital.data collection techniques were observation and questionnaire.data analysis tecniques used descriptive analytical techniques and simple linear regression analysis techniques.the population in the study was the patients of Labuang Baji Makassar Hospital as many as 65 patients and 5 representatives in each poly.With drawal samples using nonprobability sampling technique with a sample size of 40 people.Based on the results of statistical analysis of the model summary table showed that the magnitude of the correlation value or the relationship (R) of 0.790.independent variable or employee (X) s performance on the dependent variable satisfaction y was shown by the adjusted (R) Square value of 0.614.it meant that 61% of the influence of the independent variable or employee (X) s performance on the dependent variable vatient (Y) sarisfaction in Labuang Baji Makassar Hospital also from the results of the output was in a good level.